Cardiac manifestations and diagnostic imaging in pediatric inflammatory multisystem syndrome temporally associated with COVID-19: a systematic review - Octavius, Gilbert Sterling; Tan, Ricardo; Pratama, Teodorus Alfons; Budiputri, Charista Lydia; Meliani, Fellisa; Heriyanto, Rivaldo Steven; Muljadi, Rusli; Juliansen, Andry (Medical Journal of Indonesia, 2022)
BACKGROUND Several studies have reported pediatric inflammatory multisystem syndrome temporally associated with COVID-19 (PIMS-TS) cases with their cardiac manifestations, but only few studies synthesize the cardiovascular characteristics in children with PIMS-TS. However, detecting cardiac abnormalities is crucial in improving patients' outcomes and reducing mortality. This review aimed to summarize the overall symptoms, laboratory, and workup findings in PIMS-TS patients, focusing on cardiovascular manifestations. METHODS We searched 4 medical databases (PubMed, Science Direct, Medline, and Scielo) and 4 preprint databases (Medrxiv, Research Square, SSRN, and Biorxiv). The literature search was done on November 8, 2021. All case reports, case series, cross-sectional studies, cohort studies, and possible clinical trials published from December 2020 onward that studied PIMS-TS on cardiac manifestation (aged 0–18 years) were included. Studies on multisystem inflammatory syndrome in children, animal studies, and studies without full-text availability were excluded. This review was registered in PROSPERO (CRD42021194468). RESULTS 59 studies were included with a total of 698 patients. The most common cardiovascular findings were the presence of cardiogenic shock (37%) and hypotension (8.5%). Almost all laboratory values were deranged. Cardiac computed tomography scan mostly showed normal results (56%), followed by cardiomegaly with pericardial effusion (14%). Electrocardiography showed normal findings (46%), ST-segment abnormalities (32%), and abnormal T wave (12%). Echocardiography findings showed left ventricle dysfunction (40.6%), which can be considered most significant, followed by pericardial effusion together with pericarditis (11.4%) and tricuspid regurgitation (6.9%). CONCLUSIONS This review found various cardiac abnormalities that may develop during PIMS-TS. Due to these findings, we should be more vigilant and not underestimate the consequences in pediatric COVID-19 patients.